The Fifth International Survey of Critical Care Nursing Organizations: Implications for Policy. Issue 6 (22nd October 2020) - Williams, Ged; Fulbrook, Paul; Kleinpell, Ruth; Alberto, Laura
Abstract: Purpose: To examine the activities, concerns, and expectations of critical care nurses and professional critical care nursing organizations worldwide. Design: A descriptive survey methodology was used. This study is the fifth worldwide quadrennial review of its type to monitor variations in critical care nursing needs and provide robust evidence to inform policy related to critical care nursing practice. Methods: The fifth World Federation of Critical Care Nurses international survey of critical care nursing organizations was emailed to potential participants from countries with critical care nursing organizations or known critical care nurse leaders. Data were collected online. Responses were entered into SPSS version 23 software (IBM Corp., Armonk, NY, USA) and analyzed by geographical region and national wealth group. Findings: Eighty‐two national representative respondents participated in the survey, of whom two thirds ( n = 56, 68%) had an established critical care nursing organization in their country. The five most important issues identified were working conditions, teamwork, staffing levels, the need for formal practice guidelines and competencies, and wages. The top five critical care nursing organization services that were considered to be of most importance were professional representation, as well as provision of workshops and education forums, national conferences, practice standards and guidelines, and local conferences. The most important contributions expected from the World Federation of Critical Care Nurses were standards for clinical practice and professional practice, international conferences, professional representation, and study and education grants. Conclusions: The results highlight priority areas for critical care nursing and reinforce the need to address factors that can inform critical care nursing policy and practice. Results of this survey should be incorporated into strategic action plans at the national and international levels. Clinical Relevance: Nursing leaders, policymakers, and other interested stakeholders should consider these findings when planning critical care workforce requirements. Interested parties should work collaboratively to inform recommendations for further policy and action.